Land use changes and their impact on groundwater vulnerability's spatio-temporal conditions - Kintoro, Fachrurizal Sai; Adji, Tjahyo Nugroho; Widyastuti, Margaretha (Brawijaya University, 2025)
Bantul Regency, located on Java Island, is one of the areas in Indonesia with abundant groundwater sources, thus experiencing rapid urban growth. The hazard of groundwater vulnerability in this area has increased due to urban expansion that coevals with changes in land use and human population growth. The objective of this study was to analyze how groundwater vulnerability has changed due to land use conditions and what impact those changes have had. Because of the various variables associated with urban growth, the sub-districts of Bantul and Bambanglipuro were explicitly chosen as research areas. This study compared groundwater vulnerability and land use between 2009 and 2021 in a spatiotemporal manner. The vulnerability determination method used is the Susceptibility Index (SI), which consists of the parameters depth of groundwater table, groundwater recharge, aquifer media, topography, and land use. Each parameter is processed into an index of groundwater vulnerability by scoring and weighting methods. Techniques for descriptive comparative analysis are employed to ascertain how changes in land use will affect the degree of groundwater vulnerability. The results of the land use classification show that the agroforestry area has decreased while the semi-urban area has increased in 2009 and 2021. The sub-district of Bambanglipuro underwent numerous changes. On the other hand, it is known that medium and high vulnerability levels dominate groundwater vulnerability. In this instance, it is concluded that variations in land use have impacted how groundwater vulnerability levels are distributed.